Is Ankle Plantar Flexor Strength Associated With Balance and Walking Speed in Healthy People? A Systematic Review and Meta-Analysis. Issue 4 (22nd January 2021) - Tavakkoli Oskouei, Sanam; Malliaras, Peter; Jansons, Paul; Hill, Keith; Soh, Sze-Ee; Jaberzadeh, Shapour; Perraton, Luke
Abstract: Objective: The purpose of this study was to investigate the association between ankle plantar flexor muscle (PF) strength and balance and walking speed in healthy adults. Methods: Four databases (Ovid MEDLINE, Ovid EMBASE, CINAHL Plus, and SPORTDiscus) were searched from inception to December 2019. Studies with any design were included if the association between PF strength and balance and walking speed was investigated among healthy adults. Articles were screened for eligibility independently by 2 reviewers. Study characteristics and Pearson r values derived from the association between PF strength and balance and walking speed were extracted. Thirty-four studies were eligible. The main group of interest in the studies was older adults. Pearson r values were transformed to rz values using Fisher z -transformation. Meta-analysis of rz values was conducted and then back-transformed to r . Results: In older adults, PF maximal isometric strength had a positive weak association with static balance ( r  = 0.20; 95% CI = 0.08–0.32), a positive moderate association with dynamic reactive balance ( r  = 0.42; 95% CI = 0.32–0.57) and proactive balance ( r  = 0.55; 95% CI = 0.18–1.06), and a positive weak association with preferred walking speed ( r  = 0.29; 95% CI = 0.19–0.41) and maximum walking speed ( r  = 0.34; 95% CI = 0.06–0.63). In younger adults, there was a moderate association between early-phase PF rate of torque development and reactive balance (0.42 <  r  < 0.52). Conclusions: PF strength appears to be moderately associated with dynamic reactive and proactive balance and weakly associated with static balance and walking speed. This finding highlights the potential role of PF strength in dynamic reactive and proactive balance. Impact: This meta-analysis showed that ankle PF strength might be important for challenging dynamic balance tasks.